(untitled) (Journal of Tourism and Himalayan Adventures, 2023)
Sherpa and mountaineering are almost synonymous in Nepal. Once there was a time when Sherpa without mountaineering used to be regarded as half empty and mountaineering without Sherpa would be full empty. But the time has changed now and many numbers of non-Sherpa are taking part in the mountaineering sector. The increasing participation of non-Sherpa in mountaineering has supplemented this sector, on one hand, but in another, their participation has challenged and questioned the Sherpa’s legacy and monopoly in the mountaineering. In this regard, the paper analyzes the dichotomous relationships between the Sherpa and the non-Sherpa mountaineers in Nepal. The paper is based on primary data obtained through interview schedule. Sixty one (Sherpa 46 and non-Sherpa 15) mountaineers were chosen for the research. Unstructured interviews and key informants interviews along with kuragraphy are the supplementary tools for collecting the information. Interestingly, the mountaineers have mixed views regarding the participation of both the Sherpa and the non-Sherpa in the mountaineering sector. Regarding the preferences for working together in mountains 65.2 per cent Sherpa mountaineers preferred Sherpa as fellow workers but none of the Sherpa informants preferred non-Sherpa whereas 13.3 per cent non-Sherpa informants preferred Sherpa as fellow workers. Similarly, 54.3 per cent Sherpa mountaineers preferred Sherpa for hiring them in mountaineering but none of the Sherpa mountaineers preferred non-Sherpa mountaineers and vice-versa. It seems that both the Sherpa and the non-Sherpa mountaineers are ethnocentric thus a competetive rivalry looms large among them.This study is an attempt to understand the impact of the non-Sherpa’s rising participation in the mountaineering fields.